2010
DOI: 10.1186/1758-2652-13-s2-s4
|View full text |Cite
|
Sign up to set email alerts
|

Fathers and HIV: considerations for families

Abstract: BackgroundFathers are intricately bound up in all aspects of family life. This review examines fathers in the presence of HIV: from desire for a child, through conception issues, to a summary of the knowledge base on fathers within families affected by HIV.MethodsA mixed-methods approach is used, given the scarcity of literature. A review is provided on paternal and male factors in relation to the desire for a child, HIV testing in pregnancy, fatherhood and conception, fatherhood and drug use, paternal support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 101 publications
2
39
0
Order By: Relevance
“…A more recent study taking into account both heterosexual and gay/bisexual men yielded similar results (Sherr, 2010). Both studies report a reluctance of men to approach an HCP about this issue due to fear of discrimination (Sherr, 2010;Sherr & Barry, 2004). Our data showed that stigma and lack of access to healthcare resources were found to be the most important issues affecting conception planning for PLWHIV.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A more recent study taking into account both heterosexual and gay/bisexual men yielded similar results (Sherr, 2010). Both studies report a reluctance of men to approach an HCP about this issue due to fear of discrimination (Sherr, 2010;Sherr & Barry, 2004). Our data showed that stigma and lack of access to healthcare resources were found to be the most important issues affecting conception planning for PLWHIV.…”
Section: Discussionsupporting
confidence: 88%
“…A 2004 study of HIV-positive heterosexual men in London, United Kingdom, found that although nearly half of the sample population desired to conceive, most were not given medical advice and felt uninformed about the issue (Sherr & Barry, 2004). A more recent study taking into account both heterosexual and gay/bisexual men yielded similar results (Sherr, 2010). Both studies report a reluctance of men to approach an HCP about this issue due to fear of discrimination (Sherr, 2010;Sherr & Barry, 2004).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…57 The limited evidence on HIV-positive men's pregnancy intentions generally indicates that HIV-positive men tend to want children more than their HIV-positive female counterparts. [36][37][38]52,58 More research is needed to explore men's and couples' views on pregnancy desires in the context of HIV.…”
Section: Hiv and Pregnancy Desiresmentioning
confidence: 99%
“…However, accompanying the dramatic increase of HIV survival rates, particularly in high income countries since highly active antiretroviral therapy (HAART) was first introduced in 1996, an increasing number of HIV positive men are becoming fathers or are expressing interest in having children (Baumgartner and Niemi, 2013;Doyal et al 2009;Sherr, 2010).…”
Section: Introductionmentioning
confidence: 99%